Cell‐penetrating peptide conjugates of indole‐3‐acetic acid‐based DNA primase/Gyrase inhibitors as potent anti‐tubercular agents against planktonic and biofilm culture of Mycobacterium smegmatis. (23rd July 2021) - Dewangan, Rikeshwer Prasad; Singh, Meenakshi; Ilic, Stefan; Tam, Benjamin; Akabayov, Barak
Abstract: Mycobacterium tuberculosis ( Mtb ) is a pathogenic bacterium that caused 1.5 million fatalities globally in 2018. New strains of Mtb resistant to all known classes of antibiotics pose a global healthcare problem. In this work, we have conjugated novel indole‐3‐acetic acid‐based DNA primase/gyrase inhibitor with cell‐penetrating peptide via cleavable and non‐cleavable bonds. For non‐cleavable linkage, inhibitor was conjugated with peptide via an amide bond to the N‐terminus, whereas a cleavable linkage was obtained by conjugating the inhibitor through a disulfide bond. We performed the conjugation of the inhibitor either directly on a solid surface or by using solution‐phase chemistry. M. smegmatis (non‐pathogenic model of Mtb ) was used to determine the minimal inhibitory concentration (MIC) of the synthetic conjugates. Conjugates were found more active as compared to free inhibitor molecules. Strikingly, the conjugate also impairs the development of biofilm, showing a therapeutic potential against infections caused by both planktonic and sessile forms of mycobacterium species. Abstract : We conjugated novel indole‐3‐acetic acid‐based DNA primase/gyrase inhibitor with cell‐penetrating peptide. The conjugates were more active as compared to the free small‐molecule inhibitor and also impaired the development of M. smegmatis biofilm.